Use of Information Technologies in Medicine Medical Nanotechnologies (Texas Journal of Medical Science, 2022)
This article provides information on the use of information technology in medicine, the use of new and modern technologies in the detection, diagnosis and treatment of diseases, their management. There is also talk of the use of nanotechnology in the treatment of diseases in the human body.